Method for producing polyester resin molded body, and master batch

By using a masterbatch containing a polyester resin with a specific structural unit and an ester polycondensation catalyst, the problems of lower viscosity and low productivity before solid phase polymerization of the regenerated PET resin are solved, and the manufacturing of a high-quality and highly productive polyester resin molded body is achieved, and the acetaldehyde content is reduced.

CN119546668APending Publication Date: 2025-02-28아티엔스가부시키가이샤 +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380053534.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-15
Filing Date
2023-04-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art has problems with the reduction in viscosity and low productivity before solid phase polymerization of regenerated PET resins, and the device is easily contaminated during recycling and reuse. The acetaldehyde content in polyethylene terephthalate is relatively high, making it difficult to meet quality requirements.

Method used

A masterbatch containing polyester resin (A) and an ester polycondensation catalyst (B) is used. The polyester resin (A) contains 50 mol% or more of ethylene glycol or diethylene glycol structural units, and is mixed with polyethylene terephthalate at 280°C to form a sheet haze of 20%. The ester polycondensation catalyst (B) is a phosphorus, titanium or antimony catalyst for promoting solid phase polymerization.

Benefits of technology

By this method, even if a recycled polyester resin is used, a polyester resin molded body with high quality and high productivity can be obtained, which reduces the acetaldehyde content and increases the ultimate viscosity after solid phase polymerization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005239633120000081
    Figure BDA0005239633120000081
  • Figure BDA0005239633120000082
    Figure BDA0005239633120000082
  • Figure BDA0005239633120000091
    Figure BDA0005239633120000091
Patent Text Reader

Abstract

Provided is a master batch for a polyester resin molded article, which is capable of providing a polyester resin molded article having high quality and high productivity even when a regenerated polyester resin is used. A master batch for promoting solid phase polymerization of a polyester resin, the master batch containing a polyester resin (A) and an ester polycondensation catalyst (B), the polyester resin (A) contains a specific amount of a structural unit derived from ethylene glycol or the like and a structural unit derived from terephthalic acid or an ester-forming derivative thereof or the like with respect to 100 mol% of a structural unit derived from a polyol, and the master batch contains 5-60 mass% of an ester polycondensation catalyst (B). The haze of a sheet having a thickness of 1 mm formed from a 280 DEG C kneaded product of polyester resin (A) / PET resin at a mass ratio of 1 / 1 is 20% or less, and a phosphorus-based catalyst or the like is used as the ester polycondensation catalyst (B).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a polyester resin molded body and also to a masterbatch having viscosity increasing properties for a polyester resin used in the production of the polyester resin molded body. Background Art

[0002] Polyester resins are used in a wide range of fields, including synthetic fibers, films, PET bottles, mechanical parts, automobile parts, containers, electronic materials, etc., due to their excellent heat resistance and strength. The market is demanding polyester resins with better physical properties, including recycled polyester resins, and various proposals have been proposed.

[0003] Patent document 1 discloses a method for producing a masterbatch of a polyester resin, wherein a linear saturated polyester, a binder masterbatch, and a catalyst masterbatch are reacted at specific ratios, respectively, thereby increasing the melt viscosity, setting the melt flow rate to a value below a specific value, and increasing the swelling within a specific range. Patent document 2 discloses a modifier for a crystalline polyester resin, comprising: an amorphous polyester resin (I); a reactive compound (II) having two or more glycidyl groups and / or isocyanate groups per molecule and a weight average molecular weight of 200 to 500,000. Patent document 3 discloses a method, wherein a chain extender is added to a polyethylene terephthalate (PET) resin having an inherent viscosity within a specific range, and a PET resin layer having a crystalline portion of less than 15% and an amorphous portion of more than 85% is obtained through a specific manufacturing process. In addition, Patent Document 4 discloses a method in which a used PET material is extruded from a bottle collection together with a hindered hydroxyphenyl alkylphosphonic acid ester or a hindered hydroxyphenyl alkylphosphonic acid monoester by a twin-screw extruder under heating, the extrudate is formed into fine particles, and then the fine particles are solid-phase condensed in a rotary dryer under vacuum. It is shown that according to the method, the limiting viscosity after solid-phase polymerization is greatly increased. Patent Document 5 discloses a method in which a masterbatch containing a polymerization accelerator is obtained by melt-kneading polyethylene terephthalate (A) obtained by mixing terephthalic acid, isophthalic acid and ethylene glycol, performing an esterification reaction, and performing a polycondensation reaction. In addition, a method is disclosed, wherein the masterbatch is added to the polyethylene terephthalate (A) to obtain a fragmented granulated product of modified polyethylene terephthalate containing 0.1 wt% of a polymerization accelerator, followed by solid phase polymerization for 11 hours to obtain a bottle.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 01 / 094443

[0007] Patent Document 2: Japanese Patent Application Publication No. 2006-45477

[0008] Patent Document 3: Japanese Patent Application Publication No. 2012-66506

[0009] Patent Document 4: International Publication No. 96 / 11978

[0010] Patent Document 5: Japanese Patent Application Publication No. 2005-2170 Summary of the invention

[0011] Problems to be solved by the invention

[0012] In Patent Document 4, it is confirmed that the molecular weight increases after solid phase polymerization of the recycled PET resin. However, the inventors have repeatedly conducted diligent research and found that there are problems in reducing the viscosity of the recycled PET resin before solid phase polymerization and problems in productivity in terms of equipment contamination.

[0013] Dealing with the problem of plastic waste has become an important issue worldwide. In order to further promote recycling technology, high-productivity technology is urgently desired. In addition, even for recycled products, high-quality polyester resin molded products that meet moldability and color are required. In Example 1 of Patent Document 5, 7.4 ppm of acetaldehyde was detected. Since polyethylene terephthalate is used in beverage bottles, etc., high-quality polyester resin molded products that can reduce acetaldehyde content are required.

[0014] Furthermore, in the above content, the problems encountered when recycling polyester resins are described, but similar problems also occur in all polyester resins whose physical properties are to be improved.

[0015] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a method for producing a polyester resin molded body and a masterbatch of a polyester resin used in the production method, wherein even when a recycled polyester resin is used, a polyester resin molded body with high quality and high productivity can be provided.

[0016] Technical means of solving problems

[0017] The present inventors have conducted diligent studies and, as a result, have found that the problems of the present invention can be solved in the following aspects, thereby completing the present invention.

[0018] [1]: A masterbatch for promoting the solid phase polymerization of polyester resin.

[0019] The masterbatch contains a polyester resin (A) and an ester polycondensation catalyst (B).

[0020] The polyester resin (A) is a resin containing 50 mol% or more of structural units derived from ethylene glycol and / or diethylene glycol relative to 100 mol% of structural units derived from a polyol, and containing structural units derived from terephthalic acid or an ester-forming derivative thereof and / or isophthalic acid or an ester-forming derivative thereof,

[0021] The masterbatch contains 5 to 60% by mass of an ester polycondensation catalyst (B) in 100% by mass of nonvolatile components.

[0022] The haze of a sheet having a thickness of 1 mm formed from a 280° C. kneaded product of a polyester resin (A) and a polyethylene terephthalate resin in a mass ratio of 1 / 1 is 20% or less.

[0023] The ester polycondensation catalyst (B) is at least one selected from a phosphorus-based catalyst, a titanium-based catalyst, and an antimony-based catalyst.

[0024] [2]: The masterbatch according to [1], characterized in that the ester polycondensation catalyst (B) is an acid catalyst having an aromatic ring skeleton and / or an alicyclic skeleton, and

[0025] At least 1 part by mass of the ester polycondensation catalyst (B) is dissolved in 100 parts by mass of the polyester resin (A) at 250°C.

[0026] [3]: The masterbatch according to [1] or [2], characterized in that the ester polycondensation catalyst (B) is selected from alkyl phosphonates or alkyl phosphonic acid monoesters.

[0027] [4]: The masterbatch according to any one of [1] to [3], characterized in that the ester polycondensation catalyst (B) is a hindered hydroxyphenylalkylphosphonic acid ester or a hindered hydroxyphenylalkylphosphonic acid monoester.

[0028] [5]: The masterbatch according to any one of [1] to [4], characterized in that: when the molecular weight dispersion of the mixture obtained by diluting the masterbatch with the polyester resin (A) in such a manner that the ester condensation catalyst (B) becomes 1 part by mass relative to 100 parts by mass of the polyester resin (A) is set to α, and the molecular weight dispersion of the mixture when solid-phase polymerization is performed at 220°C for 10 hours is set to β, β / α is 1.00 to 1.20.

[0029] [6]: A method for producing a polyester resin molded article, comprising: a step of obtaining a masterbatch containing a polyester resin (A) and an ester polycondensation catalyst (B); a mixing step of adding at least the masterbatch to a polyester resin (C) to be modified and mixing the mixture; performing solid phase polymerization simultaneously with the mixing step or after the mixing step; and a molding step of molding the mixture after the solid phase polymerization.

[0030] The polyester resin (A) is a resin containing 50 mol% or more of structural units derived from ethylene glycol and / or diethylene glycol relative to 100 mol% of structural units derived from a polyol, and containing structural units derived from terephthalic acid or an ester-forming derivative thereof and / or isophthalic acid or an ester-forming derivative thereof,

[0031] The masterbatch contains 5 to 60% by mass of an ester polycondensation catalyst (B) in 100% by mass of the non-volatile components.

[0032] The haze of a sheet having a thickness of 1 mm formed from a 280° C. kneaded product of a polyester resin (A) and a polyethylene terephthalate resin in a mass ratio of 1 / 1 is 20% or less.

[0033] The ester polycondensation catalyst (B) is at least one selected from a phosphorus-based catalyst, a titanium-based catalyst, and an antimony-based catalyst.

[0034] [7]: The method for producing a polyester resin molded body according to [6], characterized in that the ester polycondensation catalyst (B) is selected from alkyl phosphonic acid esters or alkyl phosphonic acid monoesters.

[0035] [8]: The method for producing a polyester resin molded body according to [6] or [7], characterized in that the ester polycondensation catalyst (B) is a hindered hydroxyphenylalkylphosphonic acid ester or a hindered hydroxyphenylalkylphosphonic acid monoester.

[0036] Effects of the Invention

[0037] The present invention has the following excellent effects: a method for producing a polyester resin molded body and a masterbatch of a polyester resin used in the production method can be provided, wherein even when a recycled polyester resin is used, a polyester resin molded body with high quality and high productivity can be provided. DETAILED DESCRIPTION

[0038] Hereinafter, an example of an embodiment of the present disclosure is described. However, the present disclosure is not limited to the present embodiment, and other embodiments may also fall within the scope of the present disclosure as long as they conform to the purpose of the present disclosure. In addition, the numerical values ​​"A to B" specifically specified in this specification refer to the ranges satisfying the numerical value A and the value greater than the numerical value A, and the numerical value B and the value less than the numerical value B. In addition, the numerical values ​​specifically specified in this specification are values ​​obtained by the methods disclosed in the embodiments or examples. In addition, the sheet material, film, and plate-like body in this specification have the same meaning. As long as there are no special annotations for the various components appearing in this specification, they can be used separately and independently, or two or more can be used in combination.

[0039] 1. Polyester resin molded body

[0040] The polyester resin molded body of the present embodiment (hereinafter, also referred to as the present molded body) is obtained by adding at least a masterbatch for promoting solid phase polymerization (hereinafter, also referred to as the present masterbatch) described later to the polyester resin (C) to be modified to obtain a mixture, and subjecting the mixture to a polymerization and molding process based on solid phase polymerization. In addition, the present molded body is any molded object formed according to the purpose, and examples thereof include films, sheets, plate-like bodies, mesh-like bodies, containers, cylindrical bodies, filaments such as filaments, fibers such as nonwoven fabrics and woven fabrics. The surface of the molded body may be smooth or may have a concave-convex or complex shape. The present masterbatch is a resin composition in which an ester polycondensation catalyst (B) for polycondensation is dispersed at a high concentration, and plays the role of mixing the polyester resin (C) as a main agent with the present masterbatch at a specified ratio and modifying the polyester resin (C).

[0041] Polyester resin products are formed by various molding methods, such as uniaxial molding and biaxial molding. However, the physical properties of recycled polyester resin are lower than those of virgin polyester resin, so the productivity is greatly reduced. In addition, the scope of use of recycled polyester resin is limited due to the reduced quality.

[0042] On the other hand, by using the present molded body, even when a recycled polyester resin is used as the polyester resin (C) to be modified, a polyester resin molded body with high quality and high productivity can be obtained. The main reason for this is the use of the masterbatch disclosed in the present invention. The following is a detailed description of each component.

[0043] 1-1. Polyester resin (C)

[0044] The polyester resin (C) is a resin that is the main component of the molded body and is the resin to be modified. The polyester resin (C) may be amorphous or crystalline. In addition, the polyester resin (C) may be linear or branched. In this specification, the so-called main component refers to a component that accounts for 70% by mass or more of 100% by mass of the non-volatile components of the composition, preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more. The polyester resin (C) may be one type or a mixture of two or more types.

[0045] Typically, the polyester resin (C) includes polyester resins derived from polyols such as glycols and polycarboxylic acids such as dicarboxylic acids or ester-forming derivatives thereof, polyester resins derived from polyols such as glycols and polyhydroxycarboxylic acids such as hydroxycarboxylic acids or ester-forming derivatives thereof, or mixtures thereof.

[0046] In addition, the ester-forming derivatives of the so-called polycarboxylic acid are lower alkyl esters of dicarboxylic acids, acid halides, etc. As lower alkyl esters of dicarboxylic acids, methyl esters, ethyl esters, hydroxyethyl esters, hydroxybutyl esters, etc. can be cited. As specific examples of halides of dicarboxylic acids, acid chlorides, acid bromides, and acid iodides can be cited. In addition, polyols are alcohols having two or more hydroxyl groups in the molecule, and examples thereof include alcohols having the following structure, i.e., alcohols having a structure in which one hydroxyl group is substituted on two or more carbon atoms of a chain aliphatic hydrocarbon, a cyclic aliphatic hydrocarbon, an aromatic hydrocarbon, or a hydrocarbon compound formed by combining these.

[0047] As the diol component, various diols can be exemplified. For example, aliphatic diols such as ethylene glycol, diethylene glycol, propylene glycol, butanediol, 2-methyl-1,3-propanediol, neopentyl glycol, and hexanediol; saturated alicyclic primary diols such as 1,4-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, decahydronaphthalenedimethanol, decahydronaphthalenediethanol, norbornane dimethanol, norbornane diethanol, tricyclodecane dimethanol, tricyclodecane ethanol, tetracyclododecane dimethanol, tetracyclododecane diethanol, decahydronaphthalenedimethanol, and decahydronaphthalenediethanol; 2,6-dihydroxy-9-oxabicyclo[3,3,1]nonane, 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro[5,5]undecane( Saturated heterocyclic primary diols including cyclic ethers such as cyclohexanediol, dicyclohexyl-4,4'-diol, 2,2-bis(4-hydroxycyclohexylpropane), 2,2-bis(4-(2-hydroxyethoxy)cyclohexyl)propane, cyclopentanediol, 3-methyl-1,2-cyclopentanediol, 4-cyclopentene-1,3-diol, and adamantanediol, and aromatic diols such as bisphenol A, bisphenol S, styrene diol, 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, and 9,9'-bis(4-hydroxyphenyl)fluorene. Examples of trifunctional or higher polyols include glycerol, trimethylolpropane, and pentaerythritol.

[0048] Examples of the dicarboxylic acid or its ester-forming derivative include: fatty acid dicarboxylic acids such as adipic acid, sebacic acid, azelaic acid, dodecanedicarboxylic acid, glutaric acid, and succinic acid; aromatic dicarboxylic acids such as terephthalic acid, naphthalene dicarboxylic acid, and isophthalic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; or ester-forming derivatives thereof. Examples of trifunctional or higher polycarboxylic acids include: trimellitic acid, trimesic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, and trimellitic acid monopotassium salt.

[0049] Examples of the hydroxycarboxylic acid include lactic acid, hydroxybutyric acid, and polycaprolactone.

[0050] Specific examples of the polyester resin (C) include polyethylene terephthalate (PET), polyethylene (terephthalate / isophthalate) (I-PET), glycol-modified polyethylene terephthalate (PET-G), polybutylene terephthalate (PBT), polylactic acid (PLA), polyglycolic acid (PGA), polyethylene adipate (PEA), polyhydroxy alkanoate (PHA), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), polybutylene naphthalate (PBN), polybutylene adipate terephthalate (PEA), polyhydroxy alkanoate (PHA), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), polybutylene naphthalate (PBN), polybutylene adipate terephthalate (PET), polybutylene naphthalate (PBN), polybutylene adipate terephthalate (PET), polybutylene naphthalate (PBN), polybutylene tere ... Polyethylene terephthalate (PBAT), polybutylene succinate (PBS), polylactic acid (PLA). Polyethylene terephthalate (PET) is preferred because of its excellent transparency and easy molding process.

[0051] The polyester resin (C) may be a virgin polyester resin or a recycled polyester resin. The present production method can modify the polyester resin (C) to increase the molecular weight and increase the melt viscosity in a homogeneous manner. Therefore, it is particularly suitable for recycled polyester resins with reduced molecular weight. In addition, regardless of the type of polyester resin, it is suitable for the modification of the polyester resin according to the demand. From the perspective of obtaining a polyester resin molded body with higher quality, the polyester resin (C) is preferably a linear polyester resin.

[0052] The intrinsic viscosity (IV) of the polyester resin (C) is not particularly limited, but the lower the intrinsic viscosity (IV), the longer the polymerization time needs to be set. If the cost based on the manufacturing time is taken into consideration, a resin with an intrinsic viscosity of 0.4 dl / g or more is preferred, more preferably 0.6 dl / g or more, and further preferably 0.7 dl / g or more is preferred. The upper limit is not limited, but from the perspective of improving the properties of the polyester resin (C), it is preferably 1.2 dl / g or less. In addition, the intrinsic viscosity and melt viscosity in this specification refer to the values ​​obtained by the examples described later.

[0053] The amount of the masterbatch for promoting solid phase polymerization disclosed in the present invention added to the polyester resin (C) is not particularly limited and can be appropriately designed according to the application. For example, it is preferably 0.2 to 20 parts by mass, more preferably 0.5 to 15 parts by mass, and more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the polyester resin (C).

[0054] A polyester resin molded article can be obtained from a mixture of only the polyester resin (C) and the masterbatch. In addition, a polyester resin molded article can be obtained from a mixture to which an arbitrary component other than the polyester resin (C) and the masterbatch is added. As arbitrary additives, resins other than the components of the polyester resin (C) and the masterbatch, catalysts, chain extenders, antioxidants, antistatic agents, surfactants, flame retardants, ultraviolet absorbers, fillers, and lubricants can be exemplified without departing from the gist of the present disclosure.

[0055] 2. Masterbatch

[0056] The masterbatch disclosed in the present invention is a masterbatch for promoting the solid phase polymerization of a polyester resin. The masterbatch contains a polyester resin (A) and an ester polycondensation catalyst (B). From the viewpoint of obtaining a polyester resin molding with higher quality, it is preferred that 100% by mass of the masterbatch contain 50% by mass or more of the polyester resin (A) and the ester polycondensation catalyst (B), more preferably 60% by mass or more, and even more preferably 70% by mass or more. It is also possible to have 100% by mass of the polyester resin (A) and the ester polycondensation catalyst (B) in 100% by mass of the masterbatch. The ester polycondensation catalyst (B) is a catalyst for promoting the solid phase polymerization of the polyester resin (C).

[0057] The polyester resin (A) contains 50 mol% or more of structural units derived from ethylene glycol and / or diethylene glycol relative to 100 mol% of structural units derived from polyols, and contains structural units derived from terephthalic acid or its ester-forming derivatives and / or isophthalic acid or its ester-forming derivatives. 100% by mass of the non-volatile component of the masterbatch contains 10% to 50% by mass of the ester polycondensation catalyst (B). In 100% by mass of the non-volatile component of the masterbatch, the lower limit of the ester polycondensation catalyst (B) is more preferably 12% by mass, the upper limit is more preferably 40% by mass, and further preferably 30% by mass. Furthermore, the haze of a sheet with a thickness of 1 mm formed by a 280°C kneaded product of a polyester resin (A) / polyethylene terephthalate resin (PET resin) with a mass ratio of 1 / 1 is set to 20% or less. In addition, the ester polycondensation catalyst (B) is set to at least one selected from a phosphorus-based catalyst, a titanium-based catalyst, and an antimony-based catalyst.

[0058] Through this masterbatch, a method for manufacturing a polyester resin molded body can be provided, wherein even when a recycled polyester resin is used as the modification object, i.e., the polyester resin (C), a polyester resin molded body with high quality and high productivity can be provided. The inventors of the present invention have repeatedly conducted diligent research and found that by setting the concentration of the ester polycondensation catalyst (B) in the masterbatch to 10% by mass to 50% by mass, the acetaldehyde after solid phase polymerization of the polyester resin particles can be surprisingly reduced. It is believed that the main reason for this is that by increasing the concentration of the ester polycondensation catalyst (B) in the masterbatch, the ester polycondensation catalyst (B) can be uniformly dispersed in the polyester resin (C). It is believed that by uniformly dispersing, local polycondensation can be prevented in the subsequent solid phase polymerization process, and a high-quality polyester resin can be obtained.

[0059] Each component will be described in detail below. Each component can be used alone or in combination of two or more.

[0060] 2-1. Polyester resin (A)

[0061] The polyester resin (A) functions as a dispersion medium for dispersing the ester polycondensation catalyst (B) in the masterbatch, and plays a role in efficiently homogenizing the ester polycondensation catalyst (B) when kneading with the polyester resin (C) to be modified.

[0062] As the polyester resin (A), it is important to use a resin that satisfies the following conditions. That is, it is important to use a resin whose haze of a sheet with a thickness of 1 mm formed from a 280°C mixture of a polyester resin (A) / polyethylene terephthalate resin in a mass ratio of 1 / 1 is 20% or less. By using a polyester resin (A) that satisfies the above conditions, it is possible to achieve excellent compatibility with the polyester resin (C), improve productivity when solid-phase polymerization is performed by kneading with the polyester resin (C) to be modified, and obtain a high-quality polyester resin molded body. As for a more suitable range, the haze of a sheet with a thickness of 1 mm formed from a 280°C mixture of a polyester resin (A) / polyethylene terephthalate resin in a mass ratio of 1 / 1 is 20% or less, more preferably 15% or less, and particularly preferably 10% or less.

[0063] The polyester resin (A) having a haze of 20% or less of a sheet with a thickness of 1 mm formed from a 280°C kneaded product of a polyester resin (A) / polyethylene terephthalate resin in a mass ratio of 1 / 1 can be achieved by using a resin having high compatibility with the polyethylene terephthalate resin. As described later, a method of increasing the content of terephthalic acid or its ester-forming derivative can be exemplified. In addition, a method of increasing the dispersion of the polyester resin (A) in polyethylene terephthalate is also effective. In addition, the polyethylene terephthalate resin described in this specification refers to a resin obtained by polycondensing terephthalic acid and ethylene glycol.

[0064] The polyester resin (A) is a polyester resin containing 50 mol% or more of structural units derived from ethylene glycol and / or diethylene glycol relative to 100 mol% of structural units derived from polyols, and containing structural units derived from terephthalic acid or its ester-forming derivatives and / or isophthalic acid or its ester-forming derivatives. Such a polyester resin can be obtained by using at least terephthalic acid or its ester-forming derivatives and / or isophthalic acid or its ester-forming derivatives as polycarboxylic acids or their ester-forming derivatives, and adjusting the charge amount of ethylene glycol and / or diethylene glycol during polymerization relative to 100 mol% of polyols. In addition, "polyol" is a polyol, which refers to a compound having two or more hydroxyl groups.

[0065] Relative to 100 mol% of the structural units derived from the polyol, the structural units derived from ethylene glycol and / or diethylene glycol are more preferably 55 mol% or more, and further preferably 60 mol% or more. By including more than 50 mol% of the structural units derived from ethylene glycol, the compatibility with the polyester resin (C) becomes excellent. The upper limit is not limited and may also be 100 mol%. More preferably, it is a polyester resin containing more than 50 mol% of the structural units derived from ethylene glycol and the structural units derived from terephthalic acid or its ester-forming derivatives.

[0066] In the polyester resin (A), the structural unit derived from terephthalic acid or its ester-forming derivative and / or isophthalic acid or its ester-forming derivative is preferably 50 mol% or more, and more preferably 60 mol% or more, relative to 100 mol% of the structural unit derived from the polycarboxylic acid or its ester-forming derivative. By containing 50 mol% or more of the structural unit derived from terephthalic acid or its ester-forming derivative, the compatibility with the polyester resin (C) becomes more excellent. The upper limit is not limited and may be 100 mol%.

[0067] The other polymer components used in the polycondensation of the polyester resin (A) are not particularly limited. Preferred examples of polycarboxylic acids or their ester-forming derivatives include aromatic dicarboxylic acids such as isophthalic acid, phthalic acid, naphthalene-1,4-dicarboxylic acid or naphthalene-2,6-dicarboxylic acid, diphenyl ether-4,4'-dicarboxylic acid, diphenyl dicarboxylic acids, diphenoxy ethane diethane dicarboxylic acids, aliphatic dicarboxylic acids such as adipic acid, sebacic acid, azelaic acid, decane-1,10-dicarboxylic acid, and alicyclic dicarboxylic acids such as cyclohexane dicarboxylic acid.

[0068] Preferred examples of the polyol include aliphatic diols such as propylene glycol, trimethylene glycol, tetramethylene glycol, diethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, hexamethylene glycol, dodecamethylene glycol, and neopentyl glycol, alicyclic diols such as cyclohexanedimethanol, 2,2-bis(4'-β-hydroxyethoxyphenyl)propane, and other aromatic diols.

[0069] Examples of the polyester resin (A) include polyethylene terephthalate (PET), polyethylene (terephthalate / isophthalate) (I-PET), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sebate), polyethylene (terephthalate / decanedicarboxylic acid), polyethylene (terephthalate / naphthalate), polyethylene terephthalate (ethylene / butylene) and the like. In addition, PET-G, which is amorphized by polycondensing terephthalic acid, ethylene glycol, and 1,4-cyclohexanediol, is also suitable. As particularly suitable polyester resins (A), PET, PET-G, and I-PET can be exemplified.

[0070] The intrinsic viscosity (IV) of the polyester resin (A) is not limited, but is preferably 0.55 dl / g or more, more preferably 0.6 dl / g or more, and further preferably 0.7 dl / g or more from the viewpoint of processability and suppression of IV reduction before solid phase polymerization when added to the polyester resin (C). The upper limit is not particularly limited, but is preferably 1.2 dl / g or less from the viewpoint of ease of acquisition.

[0071] The flow initiation temperature of the polyester resin (A) is not limited, and for example, the flow initiation temperature is 180° C. or higher and 260° C. or lower. From the viewpoint of the distribution of the masterbatch in the polyester resin (C), it is preferably 200° C. to 255° C. The weight average molecular weight of the polyester resin (A) is not particularly limited as long as the flow initiation temperature is within the above range.

[0072] When a masterbatch is added to the polyester resin (C) to be modified, the melt flow rate (MFR) of the polyester resin (A) is preferably 5 g / 10 min to 100 g / 10 min, more preferably 10 g / 10 min to 50 g / 10 min, from the viewpoint of improving the dispensability of the masterbatch with respect to the polyester resin (C).

[0073] The content of the polyester resin (A) in 100% by mass of the nonvolatile components of the masterbatch can be 40% by mass to 95% by mass. By setting the content within the above range, the processability during production of the masterbatch becomes more excellent.

[0074] The acid value of the polyester resin (A) is preferably 0.5 to 35 mg / KOHg, more preferably 0.5 to 10 mg / KOHg, from the viewpoint of reducing yellowing of the polyester resin (C) after solid phase polymerization.

[0075] The weight average molecular weight of the polyester resin (A) can be, for example, 6,000 to 200,000.

[0076] 2-2. Ester polycondensation catalyst (B)

[0077] Furthermore, the ester polycondensation catalyst (B) is at least one selected from a phosphorus-based catalyst, a titanium-based catalyst, and an antimony-based catalyst. The masterbatch is a resin composition in which the ester polycondensation catalyst (B) is dispersed at a high concentration, and plays a role in modifying the polyester resin (C) by mixing it with the polyester resin (C) as a main agent at a predetermined ratio.

[0078] The inventors of the present invention have repeatedly conducted diligent research, and as a result, by setting the content of the ester polycondensation catalyst (B) to 10% to 50% by mass in the non-volatile component 100% by mass of the masterbatch, and setting it to at least one selected from a phosphorus-based catalyst, a titanium-based catalyst, and an antimony-based catalyst, the molecular weight of the polyester resin (C) to be modified can be increased and made high-molecular-weight in a shorter time than before. From the perspective of making the processability better, the ester polycondensation catalyst (B) in the non-volatile component 100% by mass of the masterbatch is preferably 45% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less. In addition, from the perspective of improving the polymerization promotion effect of the masterbatch during solid phase polymerization, the lower limit is more preferably 7% by mass, further preferably 10% by mass, and particularly preferably 12% by mass.

[0079] As a suitable example of the ester polycondensation catalyst (B), there can be exemplified an acid catalyst having an aromatic ring skeleton and / or an alicyclic skeleton, and a catalyst that dissolves at least 1 part by mass in 100 parts by mass of the polyester resin (A) at 250°C. The solubility can be confirmed by the method of the examples described later. By having an aromatic ring skeleton and / or an alicyclic skeleton in the ester polycondensation catalyst (B), the compatibility with the polyester resin (A) in the masterbatch can be improved. In addition, the compatibility with the polyester resin (C) to be modified can be improved.

[0080] As the aromatic ring skeleton, there are carbocyclic skeletons, heterocyclic skeletons and compounds formed by combining these. The number of ring-constituting carbons of the aromatic ring skeleton is preferably 3 to 20, more preferably 4 to 16, 5 to 14 or 6 to 10. As the aromatic ring skeleton, for example, a benzene ring skeleton, a naphthalene ring skeleton, and anthracene ring skeleton can be exemplified. As the alicyclic skeleton, for example, an alicyclic hydrocarbon skeleton with a carbon number of 5 to 20 can be listed, and the following can be listed: a cyclopentane skeleton, a cyclohexane skeleton, a cyclooctane skeleton, a cyclodecane skeleton, an adamantane skeleton, a norbornane skeleton, a dicyclopentane skeleton, and a tricyclodecane skeleton. In addition, it can also be a heterocycle such as morpholine.

[0081] From the viewpoint of avoiding aggregation of the ester polycondensation catalysts (B), it is preferred that the substituents of the aromatic ring skeleton and / or the alicyclic skeleton have an isobutyl group, a sec-butyl group, a tert-butyl group, or the like.

[0082] Examples of the phosphorus catalyst include phosphoric acid, trimethyl phosphate, triethyl phosphate, triphenyl phosphate, acidic methyl phosphate and other phosphoric acids or their alkyl esters or phenyl esters, phosphorous acid, trimethyl phosphite, triethyl phosphite and other phosphorous acids or their alkyl esters or phenyl esters, methylphosphonic acid, phenylphosphonic acid, benzylphosphonic acid, and methyl methylphosphonate, ethyl phenylphosphonate, benzylphosphonic acid phenyl ester and other phosphonic acids or their alkyl esters or phenyl esters, etc. From the viewpoint of the effect of increasing the molecular weight, alkylphosphonic acid esters or alkylphosphonic acid monoesters are preferred, and sterically hindered hydroxyphenylalkylphosphonic acid esters or hindered hydroxyphenylalkylphosphonic acid monoesters are more preferred.

[0083] Preferred examples of hindered hydroxyphenylalkylphosphonic acid esters or hindered hydroxyphenylalkylphosphonic acid monoesters include those represented by the general formula (1). As described below, the esters described herein also include salts containing an ester group.

[0084] [Chemistry 1]

[0085]

[0086] In the formula,

[0087] n is 1 to 6,

[0088] R 1 isopropyl, tert-butyl, cyclohexyl, or a group in which 1 to 3 hydrogen atoms of a cyclohexyl group are independently substituted with an alkyl group having 1 to 4 carbon atoms,

[0089] R 2 is a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, a cyclohexyl group, or a group in which 1 to 3 hydrogen atoms of a cyclohexyl group are independently substituted with an alkyl group having 1 to 4 carbon atoms,

[0090] R 3 is a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, a phenyl group or a naphthyl group which may have a substituent, wherein the substituent is an alkyl group having 1 to 4 carbon atoms,

[0091] R 4 is a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, a phenyl group or a naphthyl group which may have a substituent, wherein the substituent is an alkyl group having 1 to 4 carbon atoms, or represents

[0092] [Chemistry 2]

[0093]

[0094] , M r+ It is an r-valent metal cation, where r is 1 to 3.

[0095] In the general formula (1), the alkyl group having 1 to 20 carbon atoms is methyl, ethyl, propyl, butyl, pentyl, hexyl, etc., and may be linear or branched. Among these, the alkyl group having 2 to 4 carbon atoms is more preferred.

[0096] In addition, the alkyl group having 1 to 4 carbon atoms substituted on the cyclohexyl group is a branched or unbranched alkyl radical preferably having 1 to 3 substituents, particularly preferably 1 or 2 substituents. Examples of the alkyl group having 1 to 4 carbon atoms substituted on the cyclohexyl group include cyclopentyl, methylcyclopentyl, dimethylcyclopentyl, cyclohexyl, methylcyclohexyl, dimethylcyclohexyl, trimethylcyclohexyl, and tert-butylcyclohexyl.

[0097] In addition, regarding the phenyl group or naphthyl group which may have an alkyl group having 1 to 4 carbon atoms as a substituent, the number of substituents is preferably 1 to 3, and particularly preferably 1 or 2. In addition, as the suitable examples, there can be illustrated o-methylphenyl group, m-methylphenyl group or p-methylphenyl group, 2,3-dimethylphenyl group, 2,4-dimethylphenyl group, 2,5-dimethylphenyl group, 2,6-dimethylphenyl group, 3,4-dimethylphenyl group, 3,5-dimethylphenyl group, 2-methyl-6-ethylphenyl group, 4-tert-butylphenyl group, 2-ethylphenyl group, 2,6-diethylphenyl group, 1-methylnaphthyl group, 2-methylnaphthyl group, 4-methylnaphthyl group, 1,6-dimethylnaphthyl group or 4-tert-butylnaphthyl group.

[0098] In addition, the monovalent to trivalent metal cation is preferably an alkali metal cation, an alkaline earth metal cation, a heavy metal cation or an aluminum cation. Suitable examples include: Na + , K + Mg 2+ , Ca 2+ , Ba 2+ 、Zn 2+ 、Al 3+ Among them, Ca is particularly preferred. 2+ .

[0099] As R 1 or R 2 , preferably having at least one tert-butyl group.1 and R 2 It is tert-butyl.

[0100] n is preferably 1 or 2, and particularly preferably 1.

[0101] As suitable examples of the general formula (1), the following compounds can be illustrated: In the following compounds, t-Bu means a tertiary butyl group, and Et means an ethyl group.

[0102] [Chemistry 3]

[0103]

[0104] Examples of the titanium-based catalyst include titanium complexes, titanium alkoxides such as tetraisopropyl titanate, tetra-n-butyl titanate, and tetra-n-butyl titanate tetramer, titanium oxide, and titanium acetylacetonate.

[0105] Examples of the antimony catalyst include antimony oxides such as antimony trioxide and antimony pentoxide; antimony carboxylates such as antimony acetate, antimony oxalate, and potassium antimony tartrate; and antimony tri-n-butoxide and antimony triethanoloxide as antimony alcoholates.

[0106] 2-3. Other ingredients

[0107] The masterbatch may contain any components other than the polyester resin (A) and the ester polycondensation catalyst (B), for example, resins other than the above, chain extenders, antioxidants, antistatic agents, surfactants, flame retardants, ultraviolet absorbers, fillers, etc.

[0108] By extending the solid phase polymerization time, the intrinsic viscosity of the polyester resin (C) can be increased, but on the other hand, the degree of yellowing tends to worsen. The inventors and others have repeatedly conducted research and found that in order to keep the catalyst activity of the ester polycondensation catalyst (B) high and prevent yellowing at the same time, it is very effective to use an antioxidant in combination. As antioxidants, phenolic antioxidants, phosphorus antioxidants, amine antioxidants, sulfur antioxidants, etc. can be listed. In order to suppress the oxidative degradation of the ester polycondensation catalyst (B) at high temperatures, phosphorus antioxidants are preferably used. In the case of containing an antioxidant, from the viewpoint of making the heat resistance of the final molded body more excellent, the effective content of the antioxidant in 100% by mass of the masterbatch is preferably 0.01% by mass to 3% by mass, and more preferably 0.02% by mass to 1% by mass.

[0109] 2-4. Characteristics of masterbatch

[0110] The polyester resin (A) used in the masterbatch is such that the haze of a sheet having a thickness of 1 mm formed from a 280° C. mixture of polyester resin (A) / polyethylene terephthalate resin in a mass ratio of 1 / 1 is 20% or less.

[0111] The MFR of the masterbatch is more preferably 5 to 100 g / 10 min, and further preferably 10 to 50 g / 10 min, in order to improve the dispensability of the masterbatch and uniformly increase the molecular weight of the polyester resin (C). The MFR in the present disclosure is a value measured in accordance with Japanese Industrial Standards (JIS) K-7210-1:2014.

[0112] In addition, in the present masterbatch, the molecular weight of the polyester resin (A) can also be increased during the kneading of the polyester resin (A) and the ester polycondensation catalyst (B).

[0113] By using this masterbatch, a polyester resin molded body with excellent quality can be provided, which shortens the polymerization time, suppresses gelation or crosslinking, and suppresses side reactions. Preferably, when the molecular weight dispersion of the mixture obtained by diluting the masterbatch with the polyester resin (A) in a manner that the ester polycondensation catalyst (B) becomes 1 part by mass relative to 100 parts by mass of the polyester resin (A) is set to α, and the molecular weight dispersion of the mixture when solid-phase polymerization is performed at 220°C for 10 hours is set to β, β / α is 1.00 to 1.20. The upper limit of β / α is more preferably 1.15, and further preferably 1.10. In addition, the so-called molecular weight dispersion refers to the ratio of the weight average molecular weight Mw of the mixture to the number average molecular weight Mn, Mw / Mn.

[0114] 2-5. Method for producing masterbatch

[0115] Hereinafter, an example of the method for producing the present masterbatch will be described, but the method for producing the present masterbatch is not limited to the method described above.

[0116] The polyester resin (A) and the ester polycondensation catalyst (B) are weighed and put into a masterbatch production device for mixing. Examples of the masterbatch production device include a single-screw extruder, a twin-screw extruder, and a kneader-ruder. The processing temperature is usually around the melting point of the polyester resin (C) + 10°C to 40°C.

[0117] After kneading, the mixture is extruded from a masterbatch production device such as a die, and then water-cooled and cut to obtain a pelletized masterbatch. In addition to pelletization, the mixture can also be pulverized to form a powder.

[0118] 3. Method for producing polyester resin (C) molded body

[0119] The method for producing a polyester resin molded article comprises: a mixing step of adding at least the masterbatch to a polyester resin (C) to be modified and mixing the mixture; and a solid phase polymerization step simultaneously with the mixing step or after the mixing step.

[0120] In the mixing process, the masterbatch is mixed at a temperature 0°C to 30°C higher than the flow starting temperature of the polyester resin (C) so that the masterbatch becomes homogeneous. There is no particular limitation on the mixing time as long as the mixing can be performed homogeneously. For example, it is 1 minute to 20 minutes. The polyester resin particles before solid phase polymerization are dissolved in phenol / 1,1,2,2-tetrachloroethane = 1 / 1, and the IV is measured in accordance with JIS K7367-5 using an automatic viscosity measuring device "SS-600-L2" manufactured by Shibayama Scientific Instruments Manufacturing Co., Ltd., and the IV value before solid phase polymerization (IV x ), and the IV value (IV0) of the polyester resin (C) before processing used as a raw material. Ratio IV x / IV0 is preferably 0.8 or more, more preferably 0.85 or more, and still more preferably 0.90 or more. x The upper limit of / IV0 is not particularly limited, but is usually 1.00.

[0121] In the solid phase polymerization process, the polycondensation process is carried out in a solid phase at a temperature 5°C to 30°C lower than the flow start temperature of the polyester resin (C), under vacuum conditions, or in a state where high-temperature nitrogen is flowing. In the case of obtaining a substance with a lower molecular weight dispersity, the polycondensation process is carried out in a solid phase at a temperature lower than the flow start temperature, for example, 30°C to 70°C lower, within a range not lower than the glass transition temperature. For example, the following method can be exemplified: after pelletizing the recycled PET resin and the masterbatch at 280°C using a twin-screw extruder, solid phase polymerization is carried out in a rotary kiln at 220°C, for example, under a vacuum of about 1 mbar for 5 hours to 10 hours. Through solid phase polymerization, the molecular weight of the polyester resin (C) increases and the viscosity increases.

[0122] The polyester resin pellets after solid phase polymerization were dissolved in phenol / 1,1,2,2-tetrachloroethane = 1 / 1, and IV was measured using an automatic viscosity measuring device "SS-600-L2" manufactured by Shibayama Scientific Instruments Manufacturing Co., Ltd. in accordance with JIS K7367-5. The IV value after solid phase polymerization (IV y ). IV y Relative to the IV x Ratio IV y / IV x It is preferably 1.05 or more, more preferably 1.10 or more, and still more preferably 1.15 or more. Ratio IV y / IV x The upper limit of is not particularly limited, but is usually around 1.20.

[0123] Regarding the solid phase polymerization time, compared with the method of directly adding the ester polycondensation catalyst (B) in the form of powder or granules to the polyester resin (C) without using a masterbatch, the molecular weight of the polyester resin (C) can be increased in a short time. It is believed that the reason is that the ester polycondensation catalyst (B) is uniformly dispersed in the polyester resin (C), which can suppress local viscosity increase. In addition, it is believed that the compatibility of the ester polycondensation catalyst (B) and the polyester resin (C) is improved by the presence of the polyester resin (A). Therefore, it is believed that the reaction of the ester polycondensation catalyst (B) and the polyester resin (C) is promoted in the solid phase polymerization process, and the viscosity increase of the polyester resin (C) is promoted. As a result, a high-quality polyester resin can be obtained. In addition, productivity can be greatly improved.

[0124] The increase in the melt viscosity of the polyester resin (C) is preferably 5% to 40%, more preferably 7% to 30%, and further preferably 10% to 25% relative to the melt viscosity of the polyester resin (C) before processing. When the increase in the melt viscosity is within the above range, the physical properties of the polyester resin (C) can be improved without affecting the moldability.

[0125] Furthermore, the method for producing a polyester resin molded body can significantly reduce the amount of acetaldehyde (AA) generated in the production process of the polyester resin molded body. This is believed to be because the molecular weight of the polyester resin increases and decomposition products of the polyester resin with a low molecular weight that generate acetaldehyde are not generated.

[0126] The tackified polyester resin (C) can be molded into various shapes by a known method, for example, uniaxial extrusion molding, biaxial extrusion molding, injection molding, blow molding, etc. are mentioned.

[0127] Example

[0128] Hereinafter, the present disclosure will be described in more detail based on Examples, but the present disclosure is not limited to the Examples. Unless otherwise specified, in the Examples, "parts" and "%" respectively represent "parts by mass" and "mass %".

[0129] [a].Masterbatch

[0130] a-1. Polyester resin (A), etc.

[0131] The polyester resin (A) and the like used in Examples and Comparative Examples are shown below.

[0132] A-1: MA2101 (Unitika, PET)

[0133] A-2: PIFG30 (manufactured by Bell Polyester Products, I-PET)

[0134] A-3: GN001 (manufactured by Eastman Chemical, PET-G)

[0135] A-4: Synthesis Example 1 (PET)

[0136] A-5: Synthesis Example 2 (PET)

[0137] A-6: Synthesis Example 3 (PET)

[0138] A-7: Synthesis Example 4 (PET)

[0139] A-8: Synthesis Example 5 (PET)

[0140] A-9: GN5011 (manufactured by Eastman Chemical, PET-G)

[0141] A-10: SA8639-P (Unitika, PET)

[0142] A-11: Recycled PET (PET) from film

[0143] A-12: SA863JP (Made by Mitsui Chemicals, PET)

[0144] A'-13: 300FP (manufactured by WinTech Polymer, PBT)

[0145] A'-14: DN011 (manufactured by Eastman Chemical, poly1,4-cyclohexylene dimethylene terephthalate (PCT))

[0146] A'-15: Synthesis Example 6 (PBT)

[0147] A'-16: Synthesis Example 7 (PET-G)

[0148] a-2. Synthesis Example of Polyester Resin (A) etc.

[0149] <Polyester resin (A-4): Synthesis example 1>

[0150] 100 parts by mass of dimethyl terephthalate, 57.5 parts by mass of ethylene glycol, 0.06 parts by mass of magnesium acetate and 0.03 parts by mass of antimony trioxide were melted at 150°C under a nitrogen atmosphere. Thereafter, the temperature was raised to 230°C for 3 hours while stirring, methanol was distilled off, and the transesterification reaction was terminated. After the transesterification reaction was completed, an ethylene glycol solution (pH 5.0) in which 0.019 parts by mass of phosphoric acid and 0.027 parts by mass of sodium dihydrogen phosphate dihydrate were dissolved in 0.5 parts by mass of ethylene glycol was added to the reaction product. Then, a polymerization reaction was carried out at a final temperature of 285°C and a vacuum degree of 0.1 Torr to obtain a polyester resin having an intrinsic viscosity of 0.55 dl / g. Thereafter, the obtained polyester resin was dried at 160°C for 5 hours to crystallize it. Then, solid phase polymerization was carried out at 220° C. and a vacuum degree of 0.3 Torr for 6 hours to obtain a polyester resin (A-4) having an intrinsic viscosity of 0.87 dl / g and a melting point of 255° C.

[0151] <Polyester resin (A-5): Synthesis example 2>

[0152] 100 parts by mass of dimethyl terephthalate, 54.7 parts by mass of ethylene glycol, 6.0 parts by mass of cyclohexanedimethanol diol, 0.06 parts by mass of magnesium acetate and 0.03 parts by mass of antimony trioxide were melted at 150°C under a nitrogen atmosphere. Thereafter, the temperature was raised to 230°C for 3 hours while stirring, methanol was distilled off, and the transesterification reaction was terminated. After the transesterification reaction was completed, an ethylene glycol solution (pH 5.0) in which 0.019 parts by mass of phosphoric acid and 0.027 parts by mass of sodium dihydrogen phosphate dihydrate were dissolved in 0.5 parts by mass of ethylene glycol was added to the reaction product. Then, a polymerization reaction was carried out at a final arrival temperature of 285°C and a vacuum degree of 0.1 Torr to obtain a polyester resin having an intrinsic viscosity of 0.54dl / g. Subsequently, the obtained polyester resin was dried at 160°C for 5 hours to crystallize it. Then, solid phase polymerization was carried out at 220° C. and a vacuum degree of 0.3 Torr for 6 hours to obtain a polyester resin (A-5) having an intrinsic viscosity of 0.86 dl / g and a melting point of 240° C.

[0153] <Polyester resin (A-6): Synthesis example 3>

[0154] 100 parts by mass of dimethyl terephthalate, 51.8 parts by mass of ethylene glycol, 12.1 parts by mass of cyclohexanedimethanol diol, 0.06 parts by mass of magnesium acetate and 0.03 parts by mass of antimony trioxide were melted at 150°C under a nitrogen atmosphere. Thereafter, the temperature was raised to 230°C for 3 hours while stirring, methanol was distilled off, and the transesterification reaction was terminated. After the transesterification reaction was completed, an ethylene glycol solution (pH 5.0) in which 0.019 parts by mass of phosphoric acid and 0.027 parts by mass of sodium dihydrogen phosphate dihydrate were dissolved in 0.5 parts by mass of ethylene glycol was added to the reaction product. Then, a polymerization reaction was carried out at a final temperature of 285°C and a vacuum degree of 0.1Torr to obtain a polyester resin having an intrinsic viscosity of 0.54dl / g. Subsequently, the obtained polyester resin was dried at 160°C for 5 hours to crystallize it. Then, solid phase polymerization was carried out at 220° C. and a vacuum degree of 0.3 Torr for 6 hours to obtain a polyester resin (A-6) having an intrinsic viscosity of 0.86 dl / g and a melting point of 228° C.

[0155] <Polyester resin (A-7): Synthesis example 4>

[0156] 100 parts by mass of dimethyl terephthalate, 57.5 parts by mass of ethylene glycol, 12.1 parts by mass of cyclohexanedimethanol diol, 0.06 parts by mass of magnesium acetate and 0.05 parts by mass of ammonium lactate of titanium were melted at 150°C under a nitrogen atmosphere. Thereafter, the temperature was raised to 230°C over 3 hours while stirring, methanol was distilled off, and the transesterification reaction was terminated. After the transesterification reaction was completed, an ethylene glycol solution (pH 5.0) in which 0.019 parts by mass of phosphoric acid and 0.027 parts by mass of sodium dihydrogen phosphate dihydrate were dissolved in 0.5 parts by mass of ethylene glycol was added to the reaction product. Then, a polymerization reaction was carried out at a final arrival temperature of 285°C and a vacuum degree of 0.1 Torr to obtain a polyester resin having an intrinsic viscosity of 0.53dl / g. Subsequently, the obtained polyester resin was dried at 160°C for 5 hours to crystallize it. Then, solid phase polymerization was carried out at 220° C. and a vacuum degree of 0.3 Torr for 8 hours to obtain a polyester resin (A-7) having an intrinsic viscosity of 0.85 dl / g and a melting point of 255° C.

[0157] <Polyester resin (A-8): Synthesis example 5>

[0158] 100 parts by mass of dimethyl terephthalate, 54.9 parts by mass of ethylene glycol, 16.3 parts by mass of neopentyl glycol, and 0.04 parts by mass of tetrabutyl titanate were added, and an ester exchange reaction was carried out at 170°C to 220°C for 2 hours. After the ester exchange reaction was completed, the reaction system was heated from 220°C to 270°C, and the system was slowly depressurized to 500 Pa for 60 minutes. Then, a polycondensation reaction was carried out at 130 Pa or less for 55 minutes to obtain a polyester resin (A-8) having an intrinsic viscosity of 0.51 dl / g and a flow starting temperature of 170°C.

[0159] <Polyester resin (A'-15): Synthesis example 6>

[0160] 100 parts by mass of dimethyl terephthalate, 83.5 parts by mass of butanediol, 0.06 parts by mass of magnesium acetate and 0.03 parts by mass of antimony trioxide were melted at 150°C under a nitrogen atmosphere. Thereafter, the temperature was raised to 230°C for 3 hours while stirring, methanol was distilled off, and the transesterification reaction was terminated. After the transesterification reaction was completed, an ethylene glycol solution (pH 5.0) in which 0.019 parts by mass of phosphoric acid and 0.027 parts by mass of sodium dihydrogen phosphate dihydrate were dissolved in 0.5 parts by mass of ethylene glycol was added to the reaction product. Then, a polymerization reaction was carried out at a final temperature of 285°C and a vacuum degree of 0.1 Torr to obtain a polyester resin having an intrinsic viscosity of 0.53dl / g. The obtained polyester resin was dried at 140°C for 5 hours to crystallize it. Then, solid phase polymerization was carried out at 200° C. and a vacuum degree of 0.3 Torr for 8 hours to obtain a polyester resin (A′-15) having an intrinsic viscosity of 0.80 dl / g and a melting point of 234° C.

[0161] <Polyester resin (A'-16): Synthesis example 7>

[0162] 100 parts by mass of dimethyl terephthalate, 28.7 parts by mass of ethylene glycol, 67.6 parts by mass of cyclohexanedimethanol diol, 0.06 parts by mass of magnesium acetate and 0.03 parts by mass of antimony trioxide were melted at 150°C under a nitrogen atmosphere. Thereafter, the temperature was raised to 230°C for 3 hours while stirring, methanol was distilled off, and the transesterification reaction was terminated. After the transesterification reaction was completed, an ethylene glycol solution (pH 5.0) in which 0.019 parts by mass of phosphoric acid and 0.027 parts by mass of sodium dihydrogen phosphate dihydrate were dissolved in 0.5 parts by mass of ethylene glycol was added to the reaction product. Furthermore, a polymerization reaction was carried out at a final arrival temperature of 285°C and a vacuum degree of 0.1 Torr to obtain a polyester resin having an intrinsic viscosity of 0.53dl / g. The obtained polyester resin was dried at 160°C for 5 hours to crystallize it. Then, solid phase polymerization was carried out at 220° C. and a vacuum degree of 0.3 Torr for 8 hours to obtain a polyester resin (A′-16) having an intrinsic viscosity of 0.85 dl / g and a melting point of 255° C.

[0163] a-3. Haze evaluation of polyester resin (A) etc.

[0164] The polyester resin (A) and the like were mixed with polyethylene terephthalate resin (PET resin, flow start temperature 255°C, IV 0.84) at a mass ratio of 1 / 1 at 280°C, and injected into a mold at a mold temperature of 20°C using an injection molding machine (manufactured by Toshiba Machine Co., Ltd.) with an injection pressure of 60t to form a sheet having a thickness of 1 mm. The haze of the obtained sheet was measured using Haze-Gard Plus (manufactured by Gardner) in accordance with JIS K7136:2000. Haze (H x ) are as follows.

[0165] +++:H x ≦10

[0166] ++: 10<H x ≦15

[0167] +: 15<H x ≦20

[0168] NG: 20<H x

[0169] Table 1 shows the intrinsic viscosity (IV), flow initiation temperature, haze of the sheet, etc. of the polyester resin (A) etc. In addition, the content (mol%) of the structural unit derived from ethylene glycol and / or diethylene glycol in 100 mol% of the structural unit derived from the polyol constituting the polyester resin (A) etc., and the content (mol%) of the structural unit derived from terephthalic acid or its ester-forming derivative (hereinafter, also referred to as terephthalic acid etc.) and / or isophthalic acid or its ester-forming derivative (hereinafter, also referred to as isophthalic acid etc.) in 100 mol% of the structural unit derived from the polycarboxylic acid or its ester-forming derivative (hereinafter, also referred to as polycarboxylic acid etc.) constituting the polyester resin (A) are shown. These are obtained by measuring the polyester resin (A) by gas chromatography / mass spectrometry (GC / MS).

[0170]

[0171] a-4. Ester polycondensation catalyst (B), antioxidant

[0172] The ester polycondensation catalyst (B) (hereinafter also referred to as catalyst (B) and the like) and antioxidant used in Examples and Comparative Examples are shown below.

[0173] B-1: Irganox 1222 (manufactured by BASF, diethyl [[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl] phosphate)

[0174] B-2: Irganox 1425 (manufactured by BASF, calcium diethyl bis[[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphate)

[0175] B-3: Diethyl hydroxyphenylmethylenephosphonate

[0176] B-4: 2,6-dimethylbenzenesulfonic acid (manufactured by Kishida Chemical Co., Ltd.)

[0177] B-5: Antimony trioxide (manufactured by Nippon Seiko Co., Ltd.)

[0178] B-6: SPC-124 (manufactured by Sakai Chemical Co., Ltd., titanium-based catalyst)

[0179] Antioxidants

[0180] D-1: Irgafos 168 (manufactured by BASF, phosphorus-based antioxidant)

[0181] D-2: Irganox B225 (manufactured by BASF, phosphorus / phenol antioxidant)

[0182] The solubility of the ester polycondensation catalyst (B) is shown in Table 2. When 1 part by mass of the ester polycondensation catalyst (B) is added to 100 parts by mass of the polyester resin (A), and the temperature is raised to 250°C while stirring with a mechanical stirrer, if the ester polycondensation catalyst (B) cannot be visually confirmed, it is judged to be dissolved in the polyester resin (A). The dissolved catalyst is set as ○, and the insoluble catalyst is set as ×. The results are shown in Table 2.

[0183] [Table 2]

[0184] Table 2

[0185] B-1 B-2 B-3 B-4 B-5 B-6 A-1 〇 〇 〇 〇 × × A-2 〇 〇 〇 〇 × × A-3 〇 〇 〇 〇 × × A-4 〇 〇 〇 〇 × × A-5 〇 〇 〇 〇 × × A-6 〇 〇 〇 〇 × × A-7 〇 〇 〇 〇 × × A-8 〇 〇 〇 〇 × × A-9 〇 〇 〇 〇 × × A-10 〇 〇 〇 〇 × × A-11 〇 〇 〇 〇 × × A-12 〇 〇 〇 〇 × × A-17 〇 〇 〇 〇 × × A-18 〇 〇 〇 〇 × × A-19 〇 〇 〇 〇 × × A'-13 〇 〇 〇 〇 × × A'-14 〇 〇 〇 〇 × × A'-15 〇 〇 〇 〇 × × A'-16 〇 〇 〇 〇 × ×

[0186] a-5. Manufacturing of masterbatch

[0187] (Example 1-1)

[0188] 90 parts of polyester resin (A-1) and 10 parts of catalyst (B-1) were weighed and placed in a co-rotating twin-screw extruder "TEX-54α3" (L / D=52.5, discharge rate: 350 kg / hr, 3 vents) manufactured by The Japan Steel Works, Ltd. and mixed. Then, the mixture was extruded at 260° C. while being sucked and degassed from the vents under high vacuum, and cut with a pelletizer to obtain a masterbatch of Example 1-1.

[0189] (Examples 1-2 to 1-23, Comparative Examples X-1 to X-5)

[0190] The master batches of Examples 1-2 to 1-23 and Comparative Examples X-1 to X-5 were obtained by the same method as in Example 1-1 except that the materials and blending amounts (parts by mass) were changed to those shown in Table 3A and Table 3B, respectively.

[0191] a-6. Evaluation of processability of masterbatch

[0192] The strand breakage during continuous production for 1 hour using a twin-screw extruder in the manufacture of the masterbatch of the embodiment and the like was confirmed, and the productivity (processability) was evaluated according to the following criteria. The results are shown in Table 3A and Table 3B. In addition, the so-called strand breakage refers to the situation where the strand is broken and the strand cannot be pulled.

[0193] +++: No strand breakage occurred.

[0194] ++: The number of times strand breakage occurred was 1 or more and 5 or less.

[0195] +: The number of times strand breakage occurred was more than 5 times and 10 times or less.

[0196] NG: Does not meet any of the evaluation criteria. Or masterbatch cannot be produced.

[0197] a-7. Evaluation of the increase rate of molecular weight dispersion

[0198] The master batch of each example and comparative example was diluted with polyester resin (A) so that the ester polycondensation catalyst (B) was 1 part by mass relative to 100 parts by mass of polyester resin (A) to obtain a mixture. The molecular weight dispersion α of the obtained mixture was determined. Thereafter, the mixture was solid-phase polymerized at 220° C. for 10 hours to determine the molecular weight dispersion β after solid-phase polymerization. These results and the value of β / α are shown in Table 3A and Table 3B.

[0199] In addition, the number average molecular weight Mn and the weight average molecular weight Mw are obtained by dissolving recycled PET particles in a 10 mmol / L sodium trifluoroacetate / hexafluoroisopropanol (HFIP) mixed solution as a solvent, filtering the sample solution using a membrane filter, and then measuring the sample solution by gel permeation chromatography (GPC) using Shodex GPC LF-404 as a column. In addition, Mn and Mw are relative values ​​relative to the molecular weight of standard polystyrene.

[0200]

[0201]

[0202] The master batch containing 5 to 60% by mass of the ester polycondensation catalyst (B) showed excellent results in terms of processability in both Examples and Comparative Examples. In the master batches of Examples, the increase rate β / α of the molecular weight dispersion was found to be 1 to 1.2.

[0203] [b] Polyester resin particles

[0204] b-1. Polyester resin (C)

[0205] The polyester resin (C) used in Examples and Comparative Examples is shown below.

[0206] C-1: IV: 0.77, PET

[0207] C-2: IV: 0.64, PET

[0208] C-3: IV: 1.11, PET

[0209] C-4: IV: 0.41, PET

[0210] C-5: IV: 0.80, PIFG-5 (manufactured by Bell Polyester Products, I-PET)

[0211] C-6: IV: 0.80, PIFG-30 (manufactured by Bell Polyester Products, I-PET)

[0212] C-7: IV: 0.97, PIFG-5H (manufactured by Bell Polyester Products, I-PET)

[0213] C-8: IV: 0.85, Kurapet KS710-BS (manufactured by Kuraray, PET)

[0214] C-9: IV: 0.75, GN071 (manufactured by Eastman Chemical, PET-G)

[0215] C-10: IV: 0.67, GN401 (manufactured by Eastman Chemical, PET-G)

[0216] C-11: IV: 0.72, TX1001 (manufactured by Eastman Chemical, copolymeric polyester resin)

[0217] C-12: IV: 0.67, TX1801 (manufactured by Eastman Chemical, copolymeric polyester resin)

[0218] b-2. Preparation of polyester resin pellets

[0219] [Reference Example 1]

[0220] 100 parts of PET resin flakes (IV: 0.77 dl / g) from beverage bottles were extruded using a single-screw extruder (Dulmadge type screw) with a screw diameter of 40 mm manufactured by Placon Co., Ltd. of Japan at a screw speed of 90 rpm, a processing temperature of 270°C, and a discharge rate of 20 kg / h to produce polyester resin pellets of Reference Example 1.

[0221] [Example 2-1]

[0222] 100 parts of PET flake resin (IV: 0.77 dl / g) from beverage bottles and 2 parts of the masterbatch of Example 1-1 were roller-ground and extruded using a single-screw extruder (Durmacher type screw) with a screw diameter of 40 mm manufactured by Placon Co., Ltd. of Japan at a screw speed of 90 rpm, a processing temperature of 270°C, a discharge of 20 kg / h, and a residence time in the extruder of 1 minute to produce the polyester resin pellets (1) of Example 2-1.

[0223] [Examples 2-2 to 2-27, Comparative Examples Y-1 to Y-9]

[0224] Polyester resin pellets were obtained by the same method as in Example 2-1 except that the materials and blending amounts (parts by mass) were changed to those shown in Table 4A, Table 4B, and Table 5, respectively.

[0225] [Comparative Examples Y-11 and Y-12]

[0226] Polyester resin pellets were obtained in the same manner as in Example 2-1 except that a powdery ester polycondensation catalyst (B) was used instead of the masterbatch and the materials and blending amounts (parts by mass) were changed to those shown in Table 5.

[0227]

[0228]

[0229] [Table 5]

[0230] Table 5

[0231]

[0232] b-3. Evaluation of polyester resin pellets

[0233] <Intrinsic viscosity (IV) before solid phase polymerization>

[0234] The polyester resin pellets before solid phase polymerization of each example and comparative example were dissolved in phenol / 1,1,2,2-tetrachloroethane = 1 / 1, and IV was measured in accordance with JIS K7367-5 using an automatic viscosity measuring device "SS-600-L2" manufactured by Shibayama Scientific Instruments Manufacturing Co., Ltd. The IV value (IV) of each example and comparative example before solid phase polymerization was evaluated according to the following criteria: x ), and the ratio of the IV value (IV0) of the PET flake resin from beverage bottles before processing IV x / IV0. The PET flake resin derived from beverage bottles before processing refers to the polyester resin used as a raw material in Example 2-1, and the IV value of the raw material resin used as the polyester resin (C) is defined as IV0.

[0235] ++++: 0.95≦IV x / IV0

[0236] +++: 0.90≦IV x / IV0<0.95

[0237] ++: 0.85≦IV x / IV0<0.90

[0238] +:0.80≦IV x / IV0<0.85

[0239] NG:IV x / IV0<0.80

[0240] <Evaluation of increase in intrinsic viscosity (IV) after solid phase polymerization>

[0241] The polyester resin pellets of each embodiment and comparative example were used for solid phase polymerization. The solid phase polymerization conditions were set to 220°C, vacuum degree 0.3 Torr, 10 hours and 20 hours (the same conditions were also used in the following evaluations). Thereafter, the obtained reaction product was dissolved in a phenol / 1,1,2,2-tetrachloroethane = 1 / 1 solution, and the intrinsic viscosity (IV) of the polyester resin pellets was measured in accordance with JIS K7367-5 using an automatic viscosity measuring device "SS-600-L2" manufactured by Shibayama Scientific Instruments Manufacturing Co., Ltd. y ). For the IV of each embodiment and comparative example, the IV was compared with the following criteria: y IV x The increase in intrinsic viscosity was evaluated.

[0242] ++++: 1.15≦IV y / IV x

[0243] +++: 1.10≦IV y / IV x <1.15

[0244] ++: 1.08≦IV y / IV x <1.10

[0245] +:1.05≦IV y / IV x <1.08

[0246] NG:IV y / IV x <1.05

[0247] <Evaluation of acetaldehyde (AA) content>

[0248] (Water extraction method)

[0249] The polyester resin particles of each embodiment and comparative example are subjected to solid phase polymerization. Each polyester resin particle after solid phase polymerization is frozen and crushed, and after passing through a sieve of less than 1 μm, 0.2 g is weighed. 5 mL of pure water is added thereto and vibrated. Then, 1 mL of the water layer is mixed with 1 mL of DNPH (2,4-dinitrophenylhydrazine) solution as a test solution. The test solution is introduced into a high performance liquid chromatograph (HPLC), and the peak area value of the DNPH-derivatized aldehyde is determined, and a standard solution obtained by derivatizing a 15 μg / mL acetaldehyde / acetonitrile solution with DNPH is used for quantification. The evaluation criteria are as follows.

[0250] ++++: less than 0.5ppm.

[0251] +++: 0.5 ppm or more and less than 1 ppm.

[0252] ++: 1ppm or more and less than 2ppm.

[0253] +: 2ppm or more and less than 3ppm.

[0254] NG: 3ppm or more.

[0255] (Complete Dissolution Method)

[0256] After coarsely grinding each polyester resin particle after solid phase polymerization of each embodiment and comparative example, weigh 1.0 g. Add 5 mL of hexafluoroisopropanol (HFIP) thereto, let stand at room temperature overnight to completely dissolve the sample. Then, add an acetonitrile solution of DNPH (2,4-dinitrophenylhydrazine) and perform ultrasonic dispersion treatment, recover the soluble portion, wash the residue several times with an acetonitrile solution of DNPH, and then fix the volume to 25 mL. The test solution is introduced into HPLC, the peak area value of the DNPH-aldehyde is determined, and the standard solution obtained by derivatizing a 15 μg / mL acetaldehyde / acetonitrile solution with DNPH is used for quantification. The evaluation criteria are as follows.

[0257] ++++: less than 0.5ppm.

[0258] +++: 0.5 ppm or more and less than 1 ppm.

[0259] ++: 1ppm or more and less than 2ppm.

[0260] +: 2ppm or more and less than 3ppm.

[0261] NG: 3ppm or more.

[0262] <Yellowness (YI (yellow index) value)>

[0263] The polyester resin pellets after solid phase polymerization of each example and comparative example were injection molded at 270°C using an injection molding machine (manufactured by Toshiba Machine Co., Ltd., IS-100F model) to prepare a rectangular test piece of 30 mm in length × 40 mm in width × 3 mm in height. Thereafter, the L value (brightness), a value, and b value of the test piece were measured using an image spectrophotometer AU Color COLOR7x manufactured by Kurabo Co., Ltd. using a D-65 (10) standard light source, and the YI value was calculated and the yellowness was measured in accordance with JIS K7373. The evaluation criteria are as follows.

[0264] ++++: 0≦YI<5

[0265] +++: 5≦YI<10

[0266] ++: 10≦YI<15+: 15≦YI<20NG: 20≦YI[Table 6A]

[0267] Table 6A

[0268]

[0269] [Table 6B]

[0270] Table 6B

[0271]

[0272] It was confirmed that in Comparative Examples Y-7 and Y-8, which did not use a masterbatch, IV before solid phase polymerization x The decrease relative to IV0 is large. It is believed that the reason is that since master batching is not performed, there is a problem in uniform dispersion in the polyester resin (C). On the other hand, in Comparative Examples Y-1 to Y-3, etc., in which the polyester resin (A) does not have a structural unit derived from ethylene glycol, even when a master batch is used, the Mw / Mn becomes wider and a polyester resin molded body with good quality cannot be obtained. It is believed that the AA value also becomes larger due to the large amount of low molecular weight components. In addition, although IV before solid phase polymerization x Good, but IV after solid phase polymerization y In addition, even for a polyester resin containing a structural unit derived from terephthalic acid or an ester-forming derivative thereof, when the haze of a sheet having a thickness of 1 mm formed from a kneaded product of a polyester resin / polyethylene terephthalate resin at a mass ratio of 1 / 1 at 280° C. exceeds 20%, as shown in Comparative Example Y-2, it is confirmed that IV after solid phase polymerization y The increase is small and the AA value is high.

[0273] [c] Manufacture of PET bottles

[0274] c-1. Manufacturing method

[0275] The polyester resin pellets after solid phase polymerization of each example and comparative example were blow molded using a blow molding machine at 280° C. to produce 50 plastic bottles of each example and comparative example. The thickness of the plastic bottle was set to 1 mm.

[0276] c-2. Evaluation

[0277] <Blow molding properties>

[0278] Regarding the blow moldability of the plastic bottles obtained in Examples and the like, bottles having a uniform thickness of 1 mm at the longitudinally extended portion were considered good products, and the yield of good products was evaluated according to the following criteria.

[0279] ++++: The yield of good products is 100%.

[0280] +++: The yield of good products is 95% or more and less than 100%.

[0281] ++: The yield of good products is 90% or more and less than 95%.

[0282] +: The yield of good products is 85% or more and less than 90%.

[0283] NG: The yield of good products is less than 85%.

[0284] <Drop strength>

[0285] An impact test was performed on any 10 plastic bottles of good quality obtained in Examples, etc. Specifically, the plastic bottles were filled with 80% water and dropped from a height of 1 meter. The evaluation criteria were as follows.

[0286] ++++: No perforation or deformation was found in any of the 10 bottles.

[0287] +++: No perforation was observed in any of the 10 bottles, but deformation was observed in less than 5 bottles.

[0288] ++: No perforation was observed in any of the 10 bottles, but deformation was observed in 5 or more and less than 10 bottles.

[0289] +: Deformation was observed in all 10 bottles, and less than 2 bottles were perforated.

[0290] NG: Deformation was observed in all 10 bottles, and two or more bottles were perforated.

[0291] [Table 7A]

[0292] Table 7A

[0293]

[0294] [Table 7B]

[0295] Table 7B

[0296]

[0297] Industrial Applicability

[0298] The method for producing the molded body has excellent molding processability and can provide a high-quality molded body by a general processing method, so it is suitable for recycling used plastic products such as used PET bottles and fibers or plastic products generated in the production process. In addition, since the molded body has excellent quality, it can be suitably used as a high-functional resin material for a variety of applications such as fibers, films, sheets, foams, containers, electronic materials, building materials, automobile parts, and various industrial parts / products.

[0299] This application claims the priority based on Japanese patent application No. 2022-114385 filed on July 15, 2022, and all the contents disclosed therein are incorporated into this application.

Claims

1. A masterbatch for promoting solid phase polymerization of polyester resin, The masterbatch contains a polyester resin (A) and an ester polycondensation catalyst (B). The polyester resin (A) is a resin containing 50 mol% or more of structural units derived from ethylene glycol and / or diethylene glycol relative to 100 mol% of structural units derived from a polyol, and containing structural units derived from terephthalic acid or an ester-forming derivative thereof and / or isophthalic acid or an ester-forming derivative thereof, The masterbatch contains 5 to 60% by mass of an ester polycondensation catalyst (B) in 100% by mass of nonvolatile components. The haze of a sheet having a thickness of 1 mm formed from a 280° C. kneaded product of a polyester resin (A) and a polyethylene terephthalate resin in a mass ratio of 1 / 1 is 20% or less. The ester polycondensation catalyst (B) is at least one selected from a phosphorus-based catalyst, a titanium-based catalyst, and an antimony-based catalyst.

2. The masterbatch according to claim 1, characterized in that: The ester polycondensation catalyst (B) is an acid catalyst and has an aromatic ring skeleton and / or an alicyclic skeleton, and At least 1 part by mass of the ester polycondensation catalyst (B) is dissolved in 100 parts by mass of the polyester resin (A) at 250°C.

3. The masterbatch according to claim 1, characterized in that: The ester polycondensation catalyst (B) is selected from alkylphosphonic acid esters or alkylphosphonic acid monoesters.

4. The masterbatch according to claim 1, characterized in that: The ester polycondensation catalyst (B) is a hindered hydroxyphenylalkylphosphonic acid ester or a hindered hydroxyphenylalkylphosphonic acid monoester.

5. The masterbatch according to claim 1, characterized in that: When the molecular weight dispersion of the mixture obtained by diluting the masterbatch with the polyester resin (A) so that the ester polycondensation catalyst (B) becomes 1 part by mass relative to 100 parts by mass of the polyester resin (A) is α and the molecular weight dispersion of the mixture when solid phase polymerization is performed at 220° C. for 10 hours is β, β / α is 1.00 to 1.

20.

6. A method for producing a polyester resin molded body, comprising: A step of obtaining a masterbatch containing a polyester resin (A) and an ester polycondensation catalyst (B); A mixing step of adding at least the masterbatch to a polyester resin (C) to be modified and mixing the mixture; Performing solid phase polymerization simultaneously with the mixing step or after the mixing step; and The molding process is performed after solid phase polymerization. The polyester resin (A) is a resin containing 50 mol% or more of structural units derived from ethylene glycol and / or diethylene glycol relative to 100 mol% of structural units derived from a polyol, and containing structural units derived from terephthalic acid or an ester-forming derivative thereof and / or isophthalic acid or an ester-forming derivative thereof, The masterbatch contains 5 to 60% by mass of an ester polycondensation catalyst (B) in 100% by mass of the non-volatile components. The haze of a sheet having a thickness of 1 mm formed from a 280° C. kneaded product of a polyester resin (A) and a polyethylene terephthalate resin in a mass ratio of 1 / 1 is 20% or less. The ester polycondensation catalyst (B) is at least one selected from a phosphorus-based catalyst, a titanium-based catalyst, and an antimony-based catalyst.

7. The method for producing a polyester resin molded body according to claim 6, wherein: The ester polycondensation catalyst (B) is selected from alkylphosphonic acid esters or alkylphosphonic acid monoesters.

8. The method for producing a polyester resin molded body according to claim 6, wherein: The ester polycondensation catalyst (B) is a hindered hydroxyphenylalkylphosphonic acid ester or a hindered hydroxyphenylalkylphosphonic acid monoester.

Citation Information

Patent Citations

  • Modified polyethylene terephthalate and its manufacturing method

    JP2005002170A

  • Modifier for crystalline polyester resin and molded article using the same

    JP2006045477A

  • Laminated material for paper container and paper container obtained by using the same

    JP2012066506A

  • Orange inorganic pigment, covering pigment, and resin composition

    JP2022114385A

  • Increasing the molecular weight of polycondensates

    WO1996011978A1